Women's Lived Experience of Embodied Disenfranchised Grief: Loss, Betrayal, and the Double Jeopardy. (January 2019) - Garrod, Teresa; Pascal, Jan
The experience of disenfranchised grief has many twists and turns. This is particularly the case in situations that have external cause for celebration, but, in fact, contain internal loss, embodied betrayal, and double jeopardy. Focusing on a significant embodied experience, that of pregnancy after a previous pregnancy loss, we suggest that the lived experience can be vastly different from the normative experiences of joy, celebration, and "moving on." Drawing on existing literature, we find the lived experience of a subsequent pregnancy, instead reignites anxiety, guilt, grief, and loss; a profound sense of betrayal by one's body; and the liminality of the double jeopardy. Women maintain an inexpressible continuing bond to the lost baby amidst struggling with the paradox of a new pregnancy. The past seems to contradict the present, and even cloud the future. To understand such complexity, we then theorize these experiences from the Heideggerian perspectives of Being-toward-death, Angst and unheimlichkeit, and the authenticity of lived experience. We propose that phenomenological ways of seeing the world can enrich our understanding of disenfranchised grief.